COVID-19: Lost opportunities and lessons for the future - Saqr, Mohammed; Wasson, Barbara (International Journal of Health Sciences, 2020)
Humanity has witnessed outbreaks since millennia, from limited epidemics to universal pandemics that wiped millions of lives and changed the course of civilizations. The advent of vaccines has eradicated some of the serious human pathogens and attenuated many others. However, pandemics are still a fact of our modern world, as we continue to have pandemics as ravaging as HIV and as alarming as severe acute respiratory syndrome, Ebola, and Middle East respiratory syndrome. The outbreak of COVID-19 with exponential curves racing to the 3 million confirmed cases should not have been a surprise. However, we seemed to ignore the past.[1,2] Unfortunately, COVID-19 is not the world’s last pandemic and we have to learn what we have missed, and how to avoid the failures. In this article, we try to summarize the lost opportunities as well as the lessons learned, hoping we can do better in the future.